Respuesta :

Answer:

The answer is A.

Because...

[tex]3-3[/tex]

[tex]=3+-3[/tex]

[tex]=0[/tex]

Here's photo as well.

Ver imagen noyasmh

Answer:

The First Image!

Step-by-step explanation:

Given

[tex]\boxed{3+(-3}[/tex]

This gives:

[tex]\boxed{3+(-3)=3-3=0}[/tex]

You were given  3+ (-3).

This means that we count 3 places forward, then count 3 places backward.

We stop at zero.

This implies that 3+(-3) is zero

Which tells you The first option/Image  is correct!

Answered by:

AshTheNeko